Ancient Greek Infinitives and Phases1. (23rd February 2013) - Sevdali, Christina
<x xml:space="preserve">Abstract</x> Abstract. This paper is about infinitival clauses and their subjects in Ancient Greek. Ancient Greek has a tripartite paradigm that involves: (a) infinitives with overt accusative subjects (distinct from main‐clause subjects and also coreferential but emphatic), (b) infinitives with null controlled subjects that copy the case of their controller (resulting in the operation of case agreement across copula [CAAC]), and (c) infinitives with null accusative subjects that are referential and arbitrary. To account for this, I first argue that all infinitival clauses are CPs. Arguments for this include the modal distinctions among Ancient Greek infinitival clauses, the coordination of infinitival clauses with finite embedded clauses, the existence of infinitival clauses with overt complementizers, evidence from binding of infinitival subjects as well as enclitic focus particles in Ancient Greek infinitives. Although all infinitives are CPs, I argue that there is a further distinction between strong‐ and weak‐phase CPs, with phasehood being related to features in the left periphery of the clause. Infinitives with overt and null accusative subjects are strong phases, C*Ps, whereas control infinitives are weak phases—CPs that are transparent domains and can therefore allow case agreement to operate across a clause boundary. I also compare Ancient Greek to Latin and argue that the distinction between strong‐ and weak‐phase CPs is also found in the finite domain. The main implication of this proposal is that the availability of a subject is only a property of a clause, defined as a strong‐phase CP.